The Effectiveness of Independent Work Training In Improving The Performance of PKBM Ki Hajar Dewantara's Learning Citizens Ngronggot District, Nganjuk Regency - Festian Cindarbumi; Moh. Miftahul Choiri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
The research aims to find out that independent work training can improve the performance of Ki Hajar Dewantara PKBM learning residents, Ngronggot District, Nganjuk Regency. One of the efforts to improve the performance of learning citizens is through self-employed training which starts from the problem, so the point to be revealed in this study includes the implementation process that is used to support the successful implementation of the training with several stages, namely, identification and determination of training needs , the purpose of shared motivation, the purpose of teaching materials, time efficiency, study funds, training venues, supporting facilities, learning resources, learning atmosphere, supporting factors, and evaluation. This research uses a descriptive method with a qualitative approach. The data collection technique used in this research is interview observation and documentation study.From the results of data processing, it can be concluded that the implementation of self-employment training for Learning Citizens is Performance.seen from the comparison between changes in learning residents before attending self-employment training and after attending training there is an increase in performance seen from performance achievement indicators. What supports the achievement of the effectiveness of self-employment training in improving performance is good cooperation between tutors and good training participants, very high motivation and enthusiasm of Learning Citizens for self-employment training, as well as support from the local community. Keywords: Effectiveness, Training, Performance